COMMERCIAL BANKS OF UKRAINE DURING THE WAR: NEW TRENDS AND OLD PROBLEMS - Yurii A. Zadoia (European Vector of Economic Development)
The article is devoted to the analysis of the peculiarities of the activities of commercial banks in Ukraine during the period of full-scale war. Its purpose is to identify new trends in banking activity and substantiate recommendations for restructuring the work of banks and its state regulation in the post-war period. During the study, a number of hypotheses were tested. It is proved that despite the significant number of commercial banks in Ukraine, the banking services market is actually oligopolistic. Taking into account the fact that state-owned banks, whose share in the total assets of commercial banks reaches 56%, actually pursue a coordinated policy and act as a single entity, the Herfindahl-Hirschman index for the banking sector of Ukraine is more than 3000, which corresponds to an oligopolistic market. This situation is justified for martial law, but it will require changes in the post-war period. The hypothesis that the main factor affecting the size of commercial banks’ assets is monetary aggregates was confirmed. The closest correlation was found between the size of assets and the monetary aggregate M2. This gives reason to recommend regulating this monetary aggregate as a tool for state regulation of banking assets. During the full-scale war, the tendency to change the structure of banking assets, which originated back in 2020, intensified. A sharp decrease in the share of loans granted was noted, while the share of debt securities, mainly government bonds, increased. On the one hand, this is evidence of the success of the implementation of government programs to attract funds from commercial banks for borrowing and covering the state budget deficit, and on the other hand, it distracts the banking system from fulfilling its main function - mobilizing temporarily free funds and providing loans. The high yield of government bonds, the NBU discount rate, which significantly exceeds the inflation rate, make loans inaccessible to business. And since other components of the market infrastructure (for example, joint investment institutions) are underdeveloped in Ukraine, business is actually deprived of the opportunity to attract funds for the implementation of investment projects. A study of the dynamics of bank performance indicators (ROA, ROE) for the period from 2008 to 2024 showed that after the banking crisis of 2015-2018, when the banking system as a whole operated at a loss, in the following years the situation not only stabilized, but also demonstrated that banks received excess profits. This is again a consequence of high interest rates on government securities and the concentration of profits in state-owned banks. Substantiated proposals for changes in state policy in the post-war period, which should revive the lending activities of commercial banks.